Both conventionally and organically fertilized tomatoes maintain fruit quality through uncontrolled green peach aphid infestation, with a transcriptional shift towards catabolism - June Labbancz; Luke Gustafson; Preston Andrews; Amit Dhingra (PLoS ONE, 2026)
Aphids are a major pest of greenhouse-grown temperate crops, responsible for billions in crop damage yearly. As organic agriculture rapidly grows in popularity, understanding how plants grown under organic systems respond to insect pest pressure may give insights into better management practices and information about the genes of interest for crop improvement. We measured the response of tomato ( Solanum lycopersicum ) leaf and fruit transcriptome, as well as a few selected metabolites in the mature fruit, to an infestation of the generalist green peach aphid ( Myzus persicae ). The aphids were introduced approximately halfway through the lifecycle of the plants that were grown under conventional and organic fertilizer regimes. While plants provided with conventional fertilizer experienced greater aphid infestation, neither group suffered a significant loss in total yield or fruit quality. This result is likely a consequence of ample nutrient and water availability. Co-expression network analysis using WGCNA revealed that in leaf tissue, both treatment groups showed a general shift from diverse anabolic processes to catabolism, while fruit tissue experienced relatively minor changes. At the stage of infestation investigated, abscisic acid appeared to be the main phytohormone response. One coexpression network module showed a correlation with both organic fertilizer treatment and aphid infestation; its hub gene (Solyc02g078940.3) may be of interest in exploring unique responses to phloem feeding insect infestation under an organic fertilizer regime.